Comparison of efficacy of azilsartan with olmesartan in patients of hypertension: randomized controlled trial - Sharma, Deeksha; Sood, Atal; Kansal, Dinesh; Kapoor, Dhiraj; Sharma, Akshay (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Azilsartan and olmesartan are members of ARBs, used in the management of hypertension. Objective was to evaluate efficacy of azilsartan with olmesartan in patients of hypertension. Methods: A randomized, prospective, open label, comparative study was carried out in Pharmacology and Medicine department at Dr. RPGMC Kangra at Tanda, HP. The study stretched over one year and blood pressure was monitored at first, third and sixth month. Out of 69 patients, 35 patients in group A were prescribed tablet azilsartan 40 mg/day and 34 patients in group B patients were prescribed tablet olmesartan 20 mg/day. Tablet chlorthalidone 12.5 mg/day was add on in both the groups. Data was presented as mean+SD. Student’s t test was used and p value <0.05 was considered significant. Results: In group A, systolic blood pressure (SBP) values improved from baseline of 153±10 mmHg to 111±18 mmHg (p<0.001) at 3 months and 109±6.1 mmHg (p<0.001) at 6 months and diastolic blood pressure (DBP) values from baseline of 87±7 mmHg to 67.1±4.6 mmHg (p<0.001) at 3 months and 67.6±2.5 mmHg (p < 0.001) at 6 months. In group B, SBP values improved from baseline of 154±8.5 mmHg to 127±3.6 mmHg (p<0.001) at 3 months and 123±4 mmHg (p<0.001) at 6 months and DBP values from baseline of 85±6.5mm Hg to 75.7±3.3 mmHg (p<0.001) at 3 months and 73±3.3 mmHg (p<0.001) at 6 months. On intergroup comparison improvement in hypertension was better in azilsartan group (p<0.001). Conclusions: The study concluded that azilsartan is significantly better than olmesartan in controlling the hypertension.